2016
DOI: 10.3389/fpls.2016.00584
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Drought Stress and Metabolic Changes in Timothy (Phleum pratense L.) Colonized with Bacillus subtilis B26

Abstract: Drought is a major limiting factor of crop productivity worldwide and its incidence is predicted to increase under climate change. Drought adaptation of cool-season grasses is thus a major challenge to secure the agricultural productivity under current and future climate conditions. Endophytes are non-pathogenic plant-associated bacteria that can play an important role in conferring resistance and improving plant tolerance to drought. In this study, the effect of inoculation of the bacterial endophyte Bacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(128 citation statements)
references
References 89 publications
(118 reference statements)
10
115
0
3
Order By: Relevance
“…In wheat, inoculation with B. subtilis induced higher rate of CO 2 assimilation in plants exposed to water stress when compared to non-inoculated and stressed plants (Barnawal et al 2017). Gagné-Bourque et al (2016) observed positive effects on the photosynthetic rate in Timothy plants inoculated with B. subtilis and exposed to water stress. Overall, B. subtilis positively influences photosynthetic activity, being a promoter of water use efficiency in plants (Li et al 2016).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In wheat, inoculation with B. subtilis induced higher rate of CO 2 assimilation in plants exposed to water stress when compared to non-inoculated and stressed plants (Barnawal et al 2017). Gagné-Bourque et al (2016) observed positive effects on the photosynthetic rate in Timothy plants inoculated with B. subtilis and exposed to water stress. Overall, B. subtilis positively influences photosynthetic activity, being a promoter of water use efficiency in plants (Li et al 2016).…”
Section: Introductionmentioning
confidence: 81%
“…Among the most well-known PGPR, Bacillus subtilis has received particular attention because of its catabolic versatility and root colonization ability, as well as its capability to produce a large number of enzymes and metabolites that can favor plant growth under biotic and abiotic stress conditions (Gagné-Bourque et al 2016). Indeed, studies have found B. subtilis increasing the photosynthetic capacity of plants through a direct influence on stomatal conductance and cell tolerance to dehydration (Cohen et al 2008;Zhang et al 2008;Li et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress leads to the reduction in protein synthesis and an increase in hydrolysis of proteins, endorsing surge in soluble nitrogen compounds such as free amino acids (Farooq et al, 2009;Krasensky & Jonak, 2012). Proline, highly accumulated due to water stress, not only acts as an osmolyte during drought but also acts as a signalling molecule and provides defence against oxidative damage (Cheng et al, 2015;Gagné-Bourque, Bertrand, Claessens, Aliferis, & Jabaji, 2016;Hayat et al, 2012). In cell cytoplasm, it not only stabilizes protein structure but also helps in maintaining cell pH and redox status under severe stress condition by reducing the amount of singlet oxygen present, which causes lipid peroxidation of thylakoid membranes (Alia & Mohanty, 1997;Hammad & Ali, 2014;Hayat et al, 2012;Szabados & Savouré, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…in the soybean rhizosphere; Allard‐Massicotte et al , ). B. subtilis is a beneficial bacterial species that increases drought resistance in Phleum pratense L. by activating osmolyte secretion (Gagné‐Bourque et al , ). Interactions with other rhizosphere bacteria that reduce drought impact have been identified (e.g.…”
Section: Root Exudates As Stress Mediatorsmentioning
confidence: 99%